Perinatal outcomes after therapeutic rest in the latent phase of labor: A cohort study - Nanna T. Bagger; Ioanna Milidou; Sidsel Boie; Julie Glavind (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Therapeutic rest refers to the usage of medication to relieve pain in women in the latent phase of labor. Very few data are available to evaluate the safety and effect of its use. The objectives of this study were to compare perinatal and labor outcomes in women who were seeking hospital care during the latent phase of labor and who were treated either with or without therapeutic rest. Material and methods Retrospective cohort study with inclusion of nulliparous singleton pregnant women in the latent phase of labor presenting at the labor ward at Aarhus University Hospital, Denmark from May 13, 2018 to June 1, 2021. We identified two groups: women who were treated with therapeutic rest and women who were not. The primary outcomes were neonatal admission and neonatal resuscitation. Secondary outcomes included use of cardiotocography during labor, nonreactive fetal heart rate, meconium‐stained amniotic fluid, pediatric delivery room assistance, umbilical cord arterial pH and standard base excess, Apgar score at 5 minutes, interventions during labor and mode of delivery. Results In our sample of 800 women in the latent phase of labor, 414 women (52%) were treated with therapeutic rest and 386 women (48%) were not. The most frequently used (n = 206) medication for therapeutic rest was a combination of paracetamol, triazolam and codeine. We found no significant difference in neonatal admission (9.2% vs 6.5%, adjusted odds ratio [aOR] 1.2, 95% confidence interval [CI] 0.4–3.1) or neonatal resuscitation (2.4% vs 3.1%, aOR 0.7, 95% CI 0.1–4.0) between women treated with or without therapeutic rest. There were no differences between the two groups in other perinatal adverse outcomes, interventions during labor or mode of delivery. Conclusions This study found no significant association between therapeutic rest and neonatal admission or resuscitation. Our findings indicate that therapeutic rest is a safe method for managing the latent phase of labor concerning neonatal health and does not increase the risk of labor complications.